Perl best practices - Conway, Damian, 1964- (Sebastopol, CA : O'Reilly, 2005)
Many programmers code by instinct, relying on convenient habits or a "style" they picked up early on. They aren't conscious of all the choices they make, like how they format their source, the names they use for variables, or the kinds of loops they use. They're focused entirely on problems they're solving, solutions they're creating, and algorithms they're implementing. So they write code in the way that seems natural, that happens intuitively, and that feels good. But if you're serious about your profession, intuition isn't enough. Perl Best Practices author Damian Conway explains that rules.
1. Best practices -- 2. Code layout -- 3. Naming conventions -- 4. Values and expressions -- 5. Variables -- 6. Control structures -- 7. Documentation -- 8. Built-in functions -- 9. Subroutines -- 10. I/O -- 11. References -- 12. Regular expressions -- 13. Error handling -- 14. Command-line processing -- 15. Objects -- 16. Class hierarchies -- 17. Modules -- 18. Testing and debugging -- 19. Miscellanea.
Includes bibliographical references (pages 493-494) and index.
Keywords: Perl (Computer program language); Perl (Langage de programmation); COMPUTERS -- Programming Languages -- C♯; COMPUTERS -- Programming Languages -- Java; COMPUTERS -- Programming Languages -- Pascal; Perl (Computer program language); PERL; Programmatuurtechniek